Purchasing power of the minimum monthly wage and rule of law in Colombia, 1983-2013 - Cortés Pinto, José Gersaín (Universidad de La Salle. Revistas. Equidad & Desarrollo., 2013)
This paper analyzes the behavior of the purchasing power of minimum monthly wage (SMMLV) in Colombia for the 1983-2013 period, in the light of the implications resulting from the transition from the system of a state of law to a rule of law, introduced by the National Constitution of 1991 and its immediate predecessor in work matters: Law 50 of 1990. The institutional and technical profile of the decision-making process regarding the annual readjustment of the SMMLV with its corresponding results is characterized first. In the second section, the SMMLV behavior is analyzed, compared to the behavior of inflation. The third section focuses on the analysis of the purchasing power (lost or earned by the employees) in the process through an indicator built specifically for this purpose. A few conclusions and recommendations are ultimately obtained.